2005
DOI: 10.1021/bi051908a
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Lipidomics Identifies Cardiolipin Depletion in Diabetic Myocardium Linking Altered Substrate Utilization with Mitochondrial Dysfunction

Abstract: Diabetic cardiomyopathy is characterized by excessive utilization of fatty acid substrate, diminished glucose transport, and mitochondrial dysfunction. However, the chemical mechanisms linking altered substrate utilization to mitochondrial dysfunction are unknown. Herein, we use shotgun lipidomics and multidimensional mass spectrometry to identify dramatic decreases in the critical mitochondrial inner membrane lipid, cardiolipin, in diabetic murine myocardium (from 7.2 +/- 0.3 nmol/mg of protein in control hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
144
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(151 citation statements)
references
References 49 publications
5
144
1
1
Order By: Relevance
“…Peak heights represent the relative intensity (%) of the individual molecular species to the intensity of the CL internal standard. The asterisks indicate doubly charged CL plusone isotopologues whose ion peak intensities were utilized to quantify individual CL molecular species as described previously (37,78). The results indicate an increase in multiple CL species in the iPLA 2 ␥ Ϫ/Ϫ mice and especially those containing shorter chain length aliphatic chains.…”
Section: Identification Of the Heteromorphic Structures As Degeneratimentioning
confidence: 81%
See 1 more Smart Citation
“…Peak heights represent the relative intensity (%) of the individual molecular species to the intensity of the CL internal standard. The asterisks indicate doubly charged CL plusone isotopologues whose ion peak intensities were utilized to quantify individual CL molecular species as described previously (37,78). The results indicate an increase in multiple CL species in the iPLA 2 ␥ Ϫ/Ϫ mice and especially those containing shorter chain length aliphatic chains.…”
Section: Identification Of the Heteromorphic Structures As Degeneratimentioning
confidence: 81%
“…The results indicate an increase in multiple CL species in the iPLA 2 ␥ Ϫ/Ϫ mice and especially those containing shorter chain length aliphatic chains. B, the levels of total CL molecular species were calculated in comparison with internal standard after 13 C deisotoping as described previously (37,78). A 1.5-fold increase in total cardiolipin content was observed in the iPLA 2 ␥ Ϫ/Ϫ hippocampus in comparison to WT littermates (Total CL, p Ͻ 0.05).…”
Section: Identification Of the Heteromorphic Structures As Degeneratimentioning
confidence: 99%
“…Although MALDI-MS has the advantage of generating singly charged molecular ions over ESI-MS, the latter will always be the technique of choice for quantitative analysis [26]. In addition, due to instrumental limitation, we could only perform MS/MS on the precursor ions.…”
Section: Distribution Of Major CL Species In Rat Organsmentioning
confidence: 99%
“…Despite these setbacks, there have been impressive achievements during the last few years. [10][11][12][13][14][15] The main progress that has spurred advances in lipid analysis has been the development of new mass spectroscopic (MS) techniques, particularly the " soft ionization " techniques electrospray ionization (ESI) and matrix-assisted laser desorption/ionization (MALDI). Conventional mass spectral analyses used electron impact ionization, a method widely employed for small, volatile molecules but not applicable to complex biological molecules.…”
Section: Lipidomicsmentioning
confidence: 99%
“…54 Studies have indicated that degradation of mitochondrial phospholipids also occurs and could affect the cellular energy metabolism via mitochondrial functions during ischemia/reperfusion. 13 , 55 , 56 Loss of cardiolipin has been implicated as a causative factor in mitochondrial dysfunction and release of cytochrome c. 13 Another lipid alteration implicated in initiation of apoptosis is translocation of phosphatidylserine (PtdSer) from the inner to the outer leafl et of the membrane lipid bilayer. 57 , 58 We have previously demonstrated signifi cant loss of PtdCho, PtdIns, PtdSer, sphingomyelin, and cardiolipin, along with alterations in the fatty acid composition of PtdCho and PtdEtn, phosphatidyl ethanolamine, in transient cerebral ischemia.…”
mentioning
confidence: 99%